1972
DOI: 10.2337/diab.21.10.987
|View full text |Cite
|
Sign up to set email alerts
|

Perifusion of Isolated Rat Islets in Vitro: Participation of the Microtubular System in the Biphasic Release of Insulin

Abstract: A simple perifusion system for in vitro studies on the rate of insulin secretion of isolated rat islets is described. A biphasic pattern of insulin secretion was produced by glucose whereas tolbutamide stimulated only the first phase of insulin secretion. The perifusion system was used to determine the effect of anti-mitotic agents on the biphasic pattern of insulin secretion. Yinblastine and colchicine destroy microtubules whereas deuterium oxide (D Q 0) produces stabilization and interference with the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(142 citation statements)
references
References 9 publications
(15 reference statements)
11
126
1
Order By: Relevance
“…In line with these observations, nocodazole dissolved the MT skeleton including the ciliary axoneme of the MIN6m9 b-cell line, whereas colchicine did not disassemble the ciliary axoneme ( We cannot exclude an effect of colchicine on ciliogenesis, although a parsimonious explanation might be the improved visibility of ciliary axonemes because of the absence of other acetylated MT structures that otherwise mask the axonemes. These findings not only corroborate our previous results and strongly implicate a specific role for the cilium in first phase insulin release; they also offer an explanation for an almost 40-year-old observation, the differential effect of colchicine and nocodazole on insulin secretion [26][27][28] . show several phenotypes characteristic of T2DM susceptibility.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with these observations, nocodazole dissolved the MT skeleton including the ciliary axoneme of the MIN6m9 b-cell line, whereas colchicine did not disassemble the ciliary axoneme ( We cannot exclude an effect of colchicine on ciliogenesis, although a parsimonious explanation might be the improved visibility of ciliary axonemes because of the absence of other acetylated MT structures that otherwise mask the axonemes. These findings not only corroborate our previous results and strongly implicate a specific role for the cilium in first phase insulin release; they also offer an explanation for an almost 40-year-old observation, the differential effect of colchicine and nocodazole on insulin secretion [26][27][28] . show several phenotypes characteristic of T2DM susceptibility.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionsupporting
confidence: 80%
“…Early investigations into the mechanism of insulin release had revealed that the disruption of the MT network resulted in loss of insulin release, indicating that MT transport is essential for insulin secretion 25 . In contrast to MT effectors like nocodazole, treatment with colchicine abolished second phase insulin release but rendered the first phase intact [26][27][28][29] . We sought to confirm these findings and found a loss of second but not first phase insulin release for colchicine-treated MIN6m9 cells and isolated murine islets, whereas there was no insulin released in the case of treatment with nocodazole (data not shown).…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 97%
“…(2) hypothesized that Mts play an important role in secretory activity of the beta cell . These studies have been confirmed (see reference 3 for review) and extended (4)(5)(6) to show that colchicine retards the movement of newly formed insulin from the site of synthesis in the rough endoplasmic reticulum to the plasma membrane (7,8) . There is a second putative pool of insulin (9), presumably located in granules in the periphery of the beta cells, which does not require Mts for secretion.…”
supporting
confidence: 48%
“…In perifused islets of Langerhans from rats, Lacy et al suggested that the first phase of insulin secretion following stimulation with glucose may be due to the release of beta granules already associated with the microtubular system and the second phase of secretion could be the result of stored or newly synthesized granules becoming associated with the system (19). In any case, activation of the microtubular-microfilament system in the B-cell is assumed to be due to calcium ion which flows into the cell following stimulation with glucose (20).…”
Section: Discussionmentioning
confidence: 99%